Functional evaluation of cyclosporine metabolism by CYP3A4 variants and potential drug interactions - Kong, Qihui; Gao, Nanyong; Wang, Yahui; Hu, Guoxin; Qian, Jianchang; Chen, Bingbing (Frontiers in Pharmacology, 2023)
The aim of this study was to investigate the effects of CYP3A4 genetic polymorphisms on the metabolism of cyclosporine (CsA) in vitro and identify drugs that interacted with CsA. An enzymatic incubation system was developed to evaluate the kinetic parameters of CYP3A4 on CsA catalysis. A total of 132 drugs were screened to identify potential drug-drug interactions. Sprague-Dawley rats were used to determine the interaction between CsA and nimodipine and nisoldipine. The metabolite AM1 was measured by ultra-performance liquid chromatography-tandem mass spectrometry. The results demonstrated that 16 CYP3A4 variants (CYP3A4.7, 8, 9, 12, 13, 14, 16, 18, 19, 23, 24, 28, 31, 32, 33, and 34) had a lower metabolic capacity for CsA, ranging from 7.19% to 72.10%, than did CYP3A4.1. In contrast, the relative clearance rate of CYP3A4.5 was significantly higher than that of CYP3A4.1. Moreover, CYP3A4.20 lost its catalytic ability, and five other variants had no significant difference. Twelve drugs, especially calcium channel blockers, were found to remarkably inhibit the metabolism of CsA with an inhibitory rate of over 80%. Nimodipine inhibited the activity of CsA in rat liver microsomes with an IC50 of 20.54  0.93 μM, while nisoldipine had an IC50 of 16.16  0.78 μM. In vivo, three groups of Sprague-Dawley rats were administrated CsA with or without nimodipine or nisoldipine; the AUC(0-t) and AUC(0-∞) of cyclosporine were significantly increased in the nimodipine group, but not obviously in the nisoldipine group. Mechanistically, nimodipine noncompetitively inhibited the metabolism of cyclosporine. Our data showed that gene polymorphisms of CYP3A4 and nimodipine remarkably affected the metabolism of cyclosporine, thus providing a reference for the precise administration of cyclosporine.